The Islamic Education Development Concepts In The Era Of Society 5.0 - Yudi Hamsah; Irma Nur Rahmi (ASTEEC, 2023)
This article contains the concept of development in Islamic education in the era of society 5.0. Talking about education is certainly one of the ideals of all human beings to increase their dignity as a moral human being. Through education we get a variety of knowledge consisting of social, economic, religious and so on. Education that is no less important is Islamic education, because in Islamic education we are taught how to be good human beings. In this era of society, we are supported by very adequate facilities and infrastructure, of course with the presence of gadgets that we can use to learn and teach without having to spend extra energy. With just a cellphone and internet quota, students can access all forms of education through electronic media. The presence of changing times certainly makes its own development for Islamic education.